Molecular and cellular mechanisms of food allergy and food tolerance - Chinthrajah, R. Sharon; Hernandez, Joseph D.; Boyd, Scott D.; Galli, Stephen J.; Nadeau, Kari C. (Journal of allergy and clinical immunology, 2016)
Ingestion of innocuous antigens, including food proteins, normally results in local and systemic immune nonresponsiveness in a process termed oral tolerance. Oral tolerance to food proteins is likely to be intimately linked to mechanisms that are responsible for gastrointestinal tolerance to large numbers of commensal microbes. Here we review our current understanding of the immune mechanisms responsible for oral tolerance and how perturbations in these mechanisms might promote the loss of oral tolerance and development of food allergies. Roles for the commensal microbiome in promoting oral tolerance and the association of intestinal dysbiosis with food allergy are discussed. Growing evidence supports cutaneous sensitization to food antigens as one possible mechanism leading to the failure to develop or loss of oral tolerance. A goal of immunotherapy for food allergies is to induce sustained desensitization or even true long-term oral tolerance to food allergens through mechanisms that might in part overlap with those associated with the development of natural oral tolerance.